2002
DOI: 10.1101/gad.1010202
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of protein modification by ISG15 results in brain cell injury

Abstract: UBP43 (USP18) is a protease that removes the ubiquitinlike modifier ISG15 from conjugated proteins. Here we present the first report of dysregulation of protein ISG15 modification by the generation of UBP43 knockout mice. In the absence of UBP43, brain tissue showed an elevated level of ISG15 conjugates, and cellular necrosis was evident in the ependyma. Such disruption of the blood-brain barrier resulted in severe neurologic disorders. These results demonstrate that UBP43 plays a critical role in maintaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
118
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(127 citation statements)
references
References 40 publications
8
118
1
Order By: Relevance
“…It seems that tight regulation of both the ISG15 conjugation and deconjugation pathways is required to ensure proper response to cellular stress. In UBP43 knockout mouse embryonic fibroblasts (MEFs), ISG15 cleavage from cellular substrates is strongly reduced, suggesting that UBP43 is the major ISG15 isopeptidase (17). UBP43Ϫ/Ϫ MEFs demonstrate prolonged STAT1 signaling and IFN hypersensitivity, which is in accordance with data showing that signal transducer and activator of transcription 1 is an ISG15-modified protein (18).…”
supporting
confidence: 75%
“…It seems that tight regulation of both the ISG15 conjugation and deconjugation pathways is required to ensure proper response to cellular stress. In UBP43 knockout mouse embryonic fibroblasts (MEFs), ISG15 cleavage from cellular substrates is strongly reduced, suggesting that UBP43 is the major ISG15 isopeptidase (17). UBP43Ϫ/Ϫ MEFs demonstrate prolonged STAT1 signaling and IFN hypersensitivity, which is in accordance with data showing that signal transducer and activator of transcription 1 is an ISG15-modified protein (18).…”
supporting
confidence: 75%
“…The roles of different IFN-regulated genes in CNS physiology and pathophysiology such as neurodevelopment, regulation of temperature, sleep, food intake and emotion remain to be explored. In this regard, a recent study found that depletion of a newly identified IFN-stimulated gene USP18 (also named ubiquitin-specific protease 43), in which expression in brain was highly activated by peripheral IFN-a injection in our study ( Figures 1 and 4), results in the development of a severe neurological disorder. 43 Despite intense studies and the development of various drug therapies, the etiopathogenesis for common human mental disorders such as affective disorders, anxiety and schizophrenia remains poorly understood.…”
Section: Discussionsupporting
confidence: 54%
“…In this regard, a recent study found that depletion of a newly identified IFN-stimulated gene USP18 (also named ubiquitin-specific protease 43), in which expression in brain was highly activated by peripheral IFN-a injection in our study ( Figures 1 and 4), results in the development of a severe neurological disorder. 43 Despite intense studies and the development of various drug therapies, the etiopathogenesis for common human mental disorders such as affective disorders, anxiety and schizophrenia remains poorly understood. 44,45 However, recent clinical observations from patients on IFN-a therapy 10,11 and genetic studies on autoimmune mice 46 suggest a direct link between IFN-a and neuropsychiatric disorders.…”
Section: Discussionsupporting
confidence: 54%
“…As reported previously, IFN production upon LPS treatment is due to the phosphorylation of IRF3 via a Trif pathway and the induction of NF-B via a MyD88 pathway (15). We previously generated UBP43 knockout mice to study the biological function of the protein ISGylation system (6,26). We used this mouse model to investigate the possible involvement of ISGylation or UBP43 in response to LPS-mediated TLR4 signaling.…”
Section: Discussionmentioning
confidence: 99%